Intraoperative awareness during laparoscopic sleeve gastrectomy - Şen, Ozan; Karaca, Fatih Can; Zengin, Seniyye; Türkçapar, Ahmet (The European Research Journal, 2021)
Objectives: The aim of this study is to determine the incidence of intraoperative awereness (IA) in our patients who underwent laparoscopic sleeve gastrectomy (LSG) and the factors affecting the formation of this complication. Methods: Four hundred ten patients who underwent LSG between March 2018 and September 2020 were included in the study. By April 2019, we started using the Bispectral index (BIS) monitoring, which measures the depth of anesthesia in all of our LSG cases (n = 167). Patients with and without BIS monitorization were divided into two groups and compared. Results: In our series, IA was seen in 3 patients (2 males) in two different hospitals (0.7%; n = 410). They were all in the non BIS group (n = 243). The median duration of anesthesia was 120 minutes (ranging 90-180) in the non-BIS, and 113 minutes (ranging, 90-140) in the BIS group (p < 0.001). Hypotension developed in 63 patients in non-BIS and 12 patients in BIS group at the beginning of the operation (< 90/60 mm Hg). The total remifentanil infusion dose administered during the anesthesia period in the BIS group was 1310 ± 351 mcg, and 1330 ± 270 mcg in the non BIS group (p = 0.002). The effect of BIS monitorization between groups on IA, did not show statistical significance (p = 0.27). Conclusions: Anesthesia techniques that work well for patients with normal weight may not be safe and appropriate for obese patients. Especially in patients with intraoperative hypotension, it is necessary to be more careful about dose adjustment of anesthetic drugs.